The Influence Of Learning Motivation And Interest In Reading On Academic Achievement - Muhamad Nasrip (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
This study aimed to examine the effect of learning motivation and interest in reading on academic achievement. This study uses quantitative data, data collection methods through distributing questionnaires, and observations. The population of this study amounted to 400 people, using the sampling method of the Slovin formula, as many as 200 respondents. Testing using validity and reliability tests, as well as multiple linear regression analysis tests. The results of this study state that learning motivation affects learning achievement, reading interest affects learning achievement, and learning achievement and reading interest affect learning achievement. Therefore, the role of lecturers and universities is expected to design several learning programmes that can encourage both aspects in a balanced manner. Then, further research can adopt this variable or can explore and examine other variables, such as parental support, learning environment, emotional intelligence, or teaching methods, as determinants of learning achievement.